1996
DOI: 10.1136/jnnp.60.5.549
|View full text |Cite
|
Sign up to set email alerts
|

Testing of cerebrospinal compensatory reserve in shunted and non-shunted patients: a guide to interpretation based on an observational study.

Abstract: The appendix presents an introduction to the mathematical modelling of CSF pressure volume-compensation included in computerised infusion test software.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(86 citation statements)
references
References 45 publications
(20 reference statements)
1
85
0
Order By: Relevance
“…After the description of NPH by Hakim and Adams (2) many authors have developed clinical tests for measuring the capacity for CSF resorption, aiming at selecting patients for shunt surgery (1,(3)(4)(5)(6). Thus Hussey et al found that a plateau pressure (P pl ) above 22 mmHg reached during a constant rate of infusion (0.76 ml/min) in the lumbar spinal CSF space could be used as selection criterion for shunt surgery (7).…”
Section: Lumbar Infusion Test In Normal Pressure Hydrocephalusmentioning
confidence: 99%
See 2 more Smart Citations
“…After the description of NPH by Hakim and Adams (2) many authors have developed clinical tests for measuring the capacity for CSF resorption, aiming at selecting patients for shunt surgery (1,(3)(4)(5)(6). Thus Hussey et al found that a plateau pressure (P pl ) above 22 mmHg reached during a constant rate of infusion (0.76 ml/min) in the lumbar spinal CSF space could be used as selection criterion for shunt surgery (7).…”
Section: Lumbar Infusion Test In Normal Pressure Hydrocephalusmentioning
confidence: 99%
“…the amplitude at the plateau; the time to reach the steady-state plateau pressure level (T pl , min) as well as the total infusion time (T inf , min). Resistance to outflow (R out ) was calculated as (P pl ) P in )/ infusion rate, mmHg/ml/min (1,6,8,9).…”
Section: Calculations and Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with pressure differential devices often suffer excessive negative IVP in the upright position (Table 3), 3,6,11) which is thought to be important in the development of overdrainage. 4,16) Selection of a high shunt opening pressure may reduce the risk of overdrainage in the upright position, but also increases the risk of underdrainage in the supine position. In contrast, the DSV provides different opening pressures depending on the patient's posture.…”
Section: Discussionmentioning
confidence: 99%
“…In NPH and in ageing, there is evidence for both an alteration in CSF production and a decrease in the CSF absorption [31][32][33]. Even the CSF secretion is shown to be impaired in experimentally induced hydrocephalus using kaolin [34].…”
Section: Comparison With In Vivo Factsmentioning
confidence: 99%